2022
DOI: 10.3390/nu14081567
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Orotate and the Microbiome–Gut–Brain Axis Modulation: New Approaches in Psychological Comorbidities of Gastrointestinal Functional Disorders

Abstract: Magnesium orotate has been cited in the medical literature for the past three years as a possible adjuvant in some pediatric and adult gastroenterological disorders associated with dysbiosis. Studies also focus on the possibility of adding magnesium orotate in psychiatric disorders’ treatment, such as major depression and anxiety. The most relevant element in these studies is the efficiency of magnesium orotate therapy in cases with both gastroenterological and psychiatric symptoms. This article proposes a lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…47 It has been reported that the oral adjuvants of their metal compounds were effective in gut–brain axis modulation to ameliorate neurological disorders. 48–50 Besides, Il-15rα mutant mice showed the upregulation of glyoxylate and dicarboxylate metabolism, in which d -glyceric acid, glycolic acid and phosphoglycolic acid were involved. Changes in the glyoxylate and dicarboxylate metabolism were also observed in an integrated analysis of the gut microbiome and host metabolism in humans with metabolic diseases (obesity, type 2 diabetes and atherosclerotic cardiovascular disease).…”
Section: Discussionmentioning
confidence: 99%
“…47 It has been reported that the oral adjuvants of their metal compounds were effective in gut–brain axis modulation to ameliorate neurological disorders. 48–50 Besides, Il-15rα mutant mice showed the upregulation of glyoxylate and dicarboxylate metabolism, in which d -glyceric acid, glycolic acid and phosphoglycolic acid were involved. Changes in the glyoxylate and dicarboxylate metabolism were also observed in an integrated analysis of the gut microbiome and host metabolism in humans with metabolic diseases (obesity, type 2 diabetes and atherosclerotic cardiovascular disease).…”
Section: Discussionmentioning
confidence: 99%
“…Ionized serum Ca:Mg 125 and 25(OH)D3 are measures of general health that reflect CRP and HRV 126 . Serum magnesium also reflects gut microbiota diversity and gut health 127,128 .…”
Section: Vitamin D and Ca:mgmentioning
confidence: 99%
“…In studies on liver damage caused by methotrexate therapy, it was shown that magnesium Isoglycyrrhizinate (MgIG) changed the composition of the intestinal microbes by increasing the level of probiotic Lactobacillus and reducing the level of Muribaculaceae [ 153 ]. Another study demonstrated that mice on a low-magnesium diet showed a lowered number of Bifidobacterium in the gut and high levels of TNF-α and IL-6 [ 154 ].…”
Section: Micronutrients Gut Microbiome and Cancermentioning
confidence: 99%